Efficient exopolysaccharaide production by pleurotus ostreatus in submerged culture - Maftoun, Parisa (2012)
Bioactive compounds, isolated from medicinal mushroom, perform various therapeutic properties. Nowadays, Pleurotus ostreatus is the third largest commercially produced mushroom due to its rich nutrition and medicinal property. Recently, it have been reported that this mushroom can produce highly efficient immunomodulator exopolysaccharide (pleuran) in both solid state and submerged culture. Production of exopolysaccharide (EPS) in submerged culture not only reduces the production time, but also reduces many downstream steps for polysaccharides extraction and purification. In the present work, production of EPS is conducted during submerged cultivation of P. ostreatus in shake flask and in bioreactor cultures. Also the effect of C:N ratio on EPS production and cell morphology was studied. In shake flask culture, maximal polysaccharide produced was 1.25 g/L after 13 days of cultivation. Morover, it was observed that P. ostratus pellet diameter increased by time. In addition, C:N ratio of 40:1was identified as optimum C:N ratio. After this stage, cultivation process was scaled up to 16-L in situ pilot scale stirred tank bioreactor under controlled and uncontrolled pH conditions. Agitation and aeration in both cultures were 200 rpm and 1 v/v/min, respectively. The maximal cell growth and EPS production of 4.48 g/L and 1.97 g/L was obtained in controlled pH culture, respectively. Furthermore, the effect of different aeration rates ranged between 0.5 up to 2.0 v/v/min was studied. Increaseing the aeration rate resulted in significant increase in cell growth up to 7.1 g/L in 2 v/v/min aerated culture. On the other hand, the maximal volumetric and specific EPS production of about 3.1 g/L and 0.58 g/g, respectively, were obtained in 1.5 v/v/min. aerated culture. These results clearly demonstrate the scalability of pleuran production process in stirred tank bioreactor level using P. ostreatus as producer strain.